2015
DOI: 10.1371/journal.pone.0137456
|View full text |Cite
|
Sign up to set email alerts
|

The Oldest Case of Decapitation in the New World (Lapa do Santo, East-Central Brazil)

Abstract: We present here evidence for an early Holocene case of decapitation in the New World (Burial 26), found in the rock shelter of Lapa do Santo in 2007. Lapa do Santo is an archaeological site located in the Lagoa Santa karst in east-central Brazil with evidence of human occupation dating as far back as 11.7–12.7 cal kyBP (95.4% interval). An ultra-filtered AMS age determination on a fragment of the sphenoid provided an age range of 9.1–9.4 cal kyBP (95.4% interval) for Burial 26. The interment was composed of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 88 publications
0
19
0
13
Order By: Relevance
“…Archaeological research in the Lagoa Santa region identified the evidence of human groups in shelters dating back to Late Pleistocene or early Holocene (Araújo et al., ; da Gloria et al., ; Laming‐Emperaire, Prous, Vilhena de Morais, & Beltrão, ; Neves et al., ; Prous, 1992/1993; Strauss et al., ). The systematic study of more than 300 human skeletons by Neves, Prous, González‐José, Kipnis, and Powell () revealed an ancient immigration by Australo‐Melanesian people, leading to the disputed proposal of “two main biological components” for the human occupation of South America (Neves et al., , ; Neves & Pucciarelli, ).…”
Section: Regional Archaeological Settingmentioning
confidence: 99%
“…Archaeological research in the Lagoa Santa region identified the evidence of human groups in shelters dating back to Late Pleistocene or early Holocene (Araújo et al., ; da Gloria et al., ; Laming‐Emperaire, Prous, Vilhena de Morais, & Beltrão, ; Neves et al., ; Prous, 1992/1993; Strauss et al., ). The systematic study of more than 300 human skeletons by Neves, Prous, González‐José, Kipnis, and Powell () revealed an ancient immigration by Australo‐Melanesian people, leading to the disputed proposal of “two main biological components” for the human occupation of South America (Neves et al., , ; Neves & Pucciarelli, ).…”
Section: Regional Archaeological Settingmentioning
confidence: 99%
“…Strauss et al 2015;Sarasketa-Gartzia et al 2018;Villalba-Mouco et al 2018 Sr values than younger geological formations such as volcanic rock. Strontium enters ecosystems and mammal tissues without fractionation (Faure and Powell 1972;Graustein 1989), being a specific geological strontium signature incorporated into body hard tissues by substituting calcium (Ericson 1985).…”
Section: Strontium Isotope Ratios From Teeth Enamelmentioning
confidence: 87%
“…Desde o século XIX já se havia percebido que esses grupos compartilham, pelo menos até certo ponto e em contraste com os grupos Tupi (mais especificamente os Tenetehara), uma morfologia craniana semelhante (Strauss et al, 2015b). Uma interpretação possível dessa observação é a de que os grupos Gê (ou parte deles) teriam uma relação de descendência (dêmica) com os habitantes de Lagoa Santa.…”
Section: Discussionunclassified
“…Na Lapa do Santo também foi identificado um registro pictórico do início do Holoceno produzido pela técnica do picoteamento e que retrata antropomorfos fálicos . Estudos da morfologia craniana dos indivíduos da Lapa do Santo indicam forte semelhança com os crânios oriundos dos demais sítios da região de Lagoa Santa (Neves et al, 2014;Strauss et al, 2015a). Outra oposição que caracteriza os sepultamentos desarticulados incluídos no Padrão 2B é aquela entre 'dentes isolados' e 'alvéolos vazios'.…”
Section: O Contexto Arqueológico Da Lapa Do Santounclassified